INDUSTRIALISASI PASCA SURAMADU PERSPEKTIF NILAI BUDAYA - Rudi Haryanto (Karsa: Journal of Social and Islamic Culture)
Abstrac Madura ethnic posseses cultural values. Those values are implemented in terms of thought, behavior, attitude, and action. They characterize Madueres life philosophically. Modernization is an era in which science and technology become the premier requirements of any activities. It goes beyond time and place. Suramadu bridge is one of its products that will take Madura to the era of industrialization and globalizaton. As a result, all Madurese must be ready to be the host, player, as well as the pointer of Madura development. The preparation and the enhancement of both quality and quantity of human resources are a must to be facilitated. Cultural approach is still considered important to anticipate indutrialization during the development of Madura, in order to place Madurese as a respectable ethnic. Kata-kata kunci culture, industrialization, globalization